Bank Sampah Digital Kota Serang Sebagai Gerakan Lingkungan Berbasis Digital Movement - Rahmadanty, Tiara Ayu; suheri, khafifah nurulita; Nurhopia, Nida; Mulyanih, Lina (HK-Publishing, 2021)
AbstractThis study describes the Environmental Movement which is carried out on a digital basis. The merger between the digital-based environmental movement which is a movement for environmental awareness carried out through digital media that has an impact on real action in social life and becomes a new innovation in carrying out social movements. The basic thing about the presence of this social movement is that the environmental imbalance that is formed due to the accumulation of garbage has a negative impact, especially in the city of Serang, making several people form this movement. This study uses a descriptive qualitative method approach in it, by describing the presence of the Digital Waste Bank movement as a digital-based environmental movement. What's more interesting is the pandemic situation that actually made this movement present which was then implemented in the form of a digital movement with real results in the city of Serang.Keywords: Environmental Movement, Digital Waste Bank, Digital MovementÂ Â AbstrakPenelitian ini menjelaskan tentang Gerakan Lingkungan yang dilakukan dengan basis digital. Penggabungan antara Gerakan lingkungan berbasis digital yang merupakan Gerakan kepedulian terhadap lingkungan yang dilakukan melalui media digital yang berdampak pada aksi nyata dikehidupan bermasyarakat dan menjadi inovasi baru dalam melakukan Gerakan sosial. Hal mendasar hadirnya Gerakan sosial ini adalah ketidakseimbangan lingkungan yang terbentuk akibat penumpukan sampah memberikan dampak negatif khususnya di Kota Serang menjadikan beberapa masyarakat membentuk Gerakan ini. Penelitian ini menggunakan pendekatan metode kualitatif deskriptif didalamnya, dengan mendeskripsikan terkait kehadiran gerakan Bank Sampah Digital sebagai gerakan lingkungan berbasis digital. Terlebih yang menjadi menarik adalah keadaan pandemi yang justru membuat Gerakan ini hadir yang kemudian diimplementasikan dalam bentuk Gerakan digital dengan hasil Gerakan nyata di Kota Serang.Kata kunci: Gerakan Lingkungan, Bank Sampah Digital, Gerakan Digital